Consumer empowerment in Singapore's mobile phone service industry : an exploratory study. - Teo, Xin Wei. (2009)
As consumers become more sophisticated and rapid advancement in information technology paves the way for easier communication between firms and consumers, the concept of consumer empowerment is becoming increasingly important. Most of the existing research on consumer empowerment is conceptual and theoretical in nature; to date, little empirical research has been done in this area of study. This research paper aims to put forward a first step in empirically measuring consumer empowerment by proposing a method to quantify the model of consumer empowerment as conceptualised by Knott, Zwick, and Schroefer [2006], using a series of measures. Using factor analysis as our primary mode of data analysis, and survey responses from a sample of Gen Y consumers as a data source, we developed a general model to measure specific dimensions of consumer empowerment within the context of the mobile phone service industry in Singapore. The empirical model of consumer empowerment developed not only serve as a platform for further research in this area, but will also enable firms to better understand this important concept and its implications.